Sleep Needs for Children - Suzanna Smith (EDIS)
“Does your school-aged child complain about being sleepy during the day, doze off in class, or yawn a lot? Does he or she go to bed late or have trouble falling asleep? If so, your child may not be getting enough sleep.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, October 2012.